If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 + 1 = -7 Reorder the terms: 1 + 1 + 3x = -7 Combine like terms: 1 + 1 = 2 2 + 3x = -7 Solving 2 + 3x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = -7 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = -7 + -2 3x = -7 + -2 Combine like terms: -7 + -2 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 3x-2+2x+1=90 | | 30(2x)=-7 | | 30x(2)=-7 | | 30(2)=-7 | | -20(3)=4 | | X-6+1=10 | | -20(2)=-7 | | x+-7=7 | | x-(-8)=7 | | 3+(6-2k)(-7)= | | x-2x-7=0 | | -2y-4=y(y-1) | | 2x^2-6=-x | | 8a+25=3a | | x^2+18x+6=0 | | 6x+26=16x-64 | | -x-3=10 | | 4+m.5=12 | | m.2+4=8 | | -3.2y+3=18 | | 1.5x^3-x=0 | | a-3(a-4)=16 | | 4(a-3)=16 | | 2a+1.5=18.1 | | 8=-20+4x | | -6.8c=24 | | 1.5d=-4.7 | | a.5=-4 | | 14.68=b+2.57 | | -20+x=8 | | (11x+2)=(8x+20) | | {2+6}6= |